2016
DOI: 10.1021/acsbiomaterials.6b00288
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinting of Spatially Heterogeneous Collagen Constructs for Cartilage Tissue Engineering

Abstract: 3D printing of biological tissues has been of increasing interest to the biomaterials community in part because of its potential to produce spatially heterogeneous constructs. Such technology is particularly promising for orthopedic applications, which require the generation of complex geometries to match patient anatomy and complex microstructures to produce spatial heterogeneity and anisotropy. Prior research has demonstrated the capacity to create precisely shaped 3D printed constructs using biocompatible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
216
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(221 citation statements)
references
References 32 publications
4
216
0
1
Order By: Relevance
“…Although µCT is broadly used, a more simplistic technique recently described by Rhee et al . could be beneficial in cases where the overall scan size is too large and time consuming to acquire on a µCT [74]. In this technique, a hydrogel construct was lightly coated with charcoal powder to provide optical contrast before being imaged with a high-resolution, digitizing color scanner (3D Cyberware scanner) [74].…”
Section: Evaluation Of the Achieved Gradientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although µCT is broadly used, a more simplistic technique recently described by Rhee et al . could be beneficial in cases where the overall scan size is too large and time consuming to acquire on a µCT [74]. In this technique, a hydrogel construct was lightly coated with charcoal powder to provide optical contrast before being imaged with a high-resolution, digitizing color scanner (3D Cyberware scanner) [74].…”
Section: Evaluation Of the Achieved Gradientsmentioning
confidence: 99%
“…could be beneficial in cases where the overall scan size is too large and time consuming to acquire on a µCT [74]. In this technique, a hydrogel construct was lightly coated with charcoal powder to provide optical contrast before being imaged with a high-resolution, digitizing color scanner (3D Cyberware scanner) [74]. This technique provides lower resolution and lacks the internal scaffold view of a µCT scanner, but allows for a quick measurement of the geometry of a ~10 cm printed meniscus model down to 2 mm details.…”
Section: Evaluation Of the Achieved Gradientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, similar to articular cartilage, the meniscus has limited self-healing capabilities, especially in the avascular, proteoglycan-rich inner zone [16]. To repair damaged meniscus and recover normal joint function, it is necessary not only to replicate the whole tissue morphology of the native meniscus [17], but also to restore its matrix structural heterogeneity at the nano-to-microscale [18], which is critical for the tissue to perform its specialized tissue-level properties [1]. To this end, it is imperative to understand the structure-mechanical function principles of the native meniscus ECM at multiple length scales [19].…”
Section: Introductionmentioning
confidence: 99%
“…In another work by Stichler et al MSCs showed promising chondrogenic differentiation in the hybrid Hydrogels [66]. Furthermore, Rhee et al [67] developed soft cartilage tissue implants with collagen seeded with primary meniscal fibrochondrocytes, which were able to support and maintain cell growth.…”
Section: Bioprinting Of Cartilagementioning
confidence: 99%